(untitled) (Fiep Bulletin - online, 2015)
The article was based on the study of an Academy for Senior Citizens - ATI in Cocota, on Governor’s Island. This project is developed in a public square, with the goal of providing Bodybuilding activities for seniors, seeking autonomy and independence. We conducted a field study with twenty older adults who answered a questionnaire with open and closed questions, as well as an association of ideas through inducing words. Data were analyzed, resulting for they love the philosophy of ATI’s. On the responses of seniors, the words were associated with their daily life and said that after the physical activity of bodybuilding this ATI, had improvements in health. Considering the analysis of the Joint Associations of ideas between the words ATI’s Health, Seniors and Physical Activity, found that exercise Physical Activity in the square is Living Well with Health. The ATI project has brought many benefits to these seniors, like friendships, healthy body and good quality of life. It is considered important to be rethought ambiance of this space, aiming it to become airier, as are the squares, but which receive coverage, minimizing, among others, the problems of exposure to sun and rain. Thus the elderly can experience all stages of education, on the content of the classes, regardless of weather conditions.